Poder constituyente: origen político y producción positivista en el sistema colombiano - Canal Zarama, Mario (2023)
The theory of the origin of the legal system has tried to distinguish the political origin of the legislature from the product that this legislative body creates, namely, statutes. Understanding the constituent power as a law - making body, the political theory of the constitution enables us to characterize this power as the product of a political proces s of social formation that organizes and establishes the state. The constitution and law are seen as instruments of this process and, once created, they continue to exist and become self - explanatory.